Efektivitas Pembelajaran Dengan Model Seven Jumps Berbantuan Wag Di Masa Pandemi Covid-19 - Hartutik Hartutik; Prabandari C.D; Astuti Andarweni; Epilia F (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
Seeing the root of the problem of student independence during the Covid-19 pandemic, implementing the effectiveness of learning with the Seven Jumps model assisted by the whatsapp group during the Covid-19 Pandemic is the aim of this research. This type of research approach is a qualitative and quantitative experiment carried out online with the Seven Jumps learning model assisted by WhatsApp groups. Data was collected by questionnaires, observation sheets and tests. Valid device tests come from expert perceptions, test the effectiveness of learning with statistical tests of the effect of regression and comparative t tests. The results showed that the root problems and constraints for student independence in utilizing information technology to achieve the expected competencies were: low self-motivation to learn, self-assessment ability, self-discipline, self-control, responsibility, pattern-learning ability, self-reliance in designing appropriate learning objectives, design implementation strategies, monitoring the progress of learning outcomes, coordination of learning methods, and the need for guidance in finding learning resources, implementing independent learning with the Seven Jumps model assisted by the whatsapp group is effective. This is indicated by: a) there is a positive influence of independent learning on problem solving ability of 60.8%, b) The gain test to measure the effectiveness of the pretest and posttest is 0.52 in the medium category and the effectiveness is sufficient. The Seven Jumps method can be implemented boldly during the Covid-19 Pandemic.